The Role of Regulation on Entry : Evidence from the Italian Provinces - Bripi, Francesco (Published by Oxford University Press on behalf of the World Bank, 2018)
This paper studies the effects of differences in local administrative burdens in Italy in the years 2005–2007 preceding a major reform that sped up firm registration procedures. Combining regulatory data from a survey on Italian provinces before the reform (costs and time to start a business) with industry-level entry rates of limited liability firms, I explore the effects of regulatory barriers on the average of the annual entry rates across industries with different natural propensities to enter the market. The estimates of the cross-sectional analysis show that lengthier and, to some extent, more costly procedures reduced entry in sectors with naturally high entry. A one-day delay in registration procedures reduces the entry rate in highly dynamic sectors by more than 1 percent. These results hold when I include measures of local financial development and of efficiency of bankruptcy procedures.